PERSPECTIVES OF BACTERIOPHAGES PREPARATIONS USE IN THERAPEUTIC AND PREVENTIVE PURPOSES - Baranovskiy, M.; Boichenko, M. (Science-based technologies, 2014)
Many years of antibiotics use for the treatment of various diseases has led to the emergence of multidrug-resistant bacterial strains. According to WHO, more than 60 % of pathogens are resistant to major antibiotics, and in 10–20 years almost all will acquire antimicrobial resistance. The reasons for the rapid adaptation of microorganisms to antibiotics may include continual, unreasonable using of antibiotics for self-medication, and when they are not effective: URTI, cough, flu; the total use of antibiotics in agriculture to prevent the development of diseases that can be transmitted to humans through food; the ability of bacteria to mutate and adapt quickly to different antibacterial drugs; not complete course of antibiotics. In this situation, a decent alternative to antibiotics in the treatment of many diseases of bacterial origin can make bacteriophages opened nearly a century ago. The modern practice of applying bacteriophage preparations used for the prevention and treatment of infectious lesions of the gastrointestinal tract; purulent-inflammatory diseases of the eyes, ears, nose, mouth, throat, lungs; surgical infections; burn wounds; urogenital infections and other diseases. The main benefits of bacteriophages: are highly specific; have no contraindications to use; do not cause the development of microbial resistance; have no toxic, allergic, and teratogenic effects; they can also be used in combination with other preparations, including antibiotics and probiotics.